Benchmarking the digital divide using a multi-level outranking framework: Evidence from EBRD countries of operation - Petrović, Marijana; Bojković, Nataša; Anić, Ivan; Petrović, Dalibor (Government Information Quarterly, 2012)
The paper proposes an innovative procedure for benchmarking the digital divide. The study demonstrates the potential of an outranking approach as an alternative to the commonly used ranking models based on Composite Indices (CIs). To fulfill the objectives of the benchmarking process, an ELECTRE-based (ELimination Et Choix Traduisant la REalité; Elimination and Choice Corresponding to Reality) multi-level outranking (ELECTRE MLO) method is developed. The proposed approach improves on previous methods of benchmarking the digital divide in two ways: by classifying countries into hierarchical levels of performance and by identifying corresponding benchmarks for less successful ones. The method is applied to 29 EBRD (European Bank for Reconstruction and Development) countries of operation. The results are visualized in the form of a relation tree, thus providing clear insights for policy-makers regarding how countries stand relative to each other.
Keywords: Benchmarking; Digital divide; EBRD countries; ELECTRE; Multi-level outranking